VENTRICULAR SEPTAL DEFECT: A COMPREHENSIVE LITERATURE REVIEW OF PATHOPHYSIOLOGY, DIAGNOSIS, AND TREATMENT - Wiktoria Szumlińska; Julia Procyk; Marta Danuta Cendrowska; Aleksandra Klukowska; Beata Choromańska; Karolina Stępień; Justyna Berent; Paulina Rzepa; Barbara Ponitka; Julia Maszewska; Szymon Milnerowicz; Łukasz Brzost (International Journal of Innovative Technologies in Social Science, 2025)
Background: Ventricular septal defect (VSD) is the most prevalent congenital heart defect, characterized by an abnormal communication between the ventricles, leading to a left-to-right shunt. Its clinical spectrum ranges from asymptomatic small defects to large shunts causing heart failure, pulmonary hypertension, or Eisenmenger syndrome. Early diagnosis and appropriate management are critical to prevent long-term complications. Methods: This literature review synthesizes current evidence on the classification, pathophysiology, diagnostic modalities, treatment options, and long-term outcomes of VSD. A comprehensive analysis of peer-reviewed articles and clinical guidelines was conducted to present up-to-date insights into the multidisciplinary approach to VSD care. Results: Anatomical subtypes of VSD vary in clinical significance, risk of complications, and management strategies. Advances in imaging, particularly echocardiography and cardiac MRI, have improved diagnostic precision. While small defects often resolve spontaneously and are managed conservatively, large or symptomatic defects may require surgical or transcatheter closure. Surgical repair remains the standard for most cases, but selected muscular and perimembranous defects can be treated percutaneously. Long-term follow-up is essential due to risks of arrhythmias, conduction block, residual shunts, or valve dysfunction. Emerging technologies—including biodegradable devices, minimally invasive surgery, and experimental gene therapy—may reshape future management paradigms. Conclusions: VSD management requires individualized, anatomy-guided decision-making supported by multidisciplinary expertise. Technological progress has expanded therapeutic options, yet lifelong surveillance remains necessary to mitigate late complications and optimize outcomes.